Easy anchoring and smaller skin incision procedure for neuronavigation-based frameless stereoelectroencephalography. (April 2020) - Fujimoto, Ayataka; Sakakura, Kazuki; Ichikawa, Naoki; Okanishi, Tohru
Highlights: Easy anchoring technique with titanium plate. SEEG using neuronavigation. Smaller skin incision. Abstract: Epilepsy surgery uses both depth electrodes (DEs) and subdural electrodes (SE). DEs have mainly been developed and used in Europe. As we are able to use the DEs safely due to the current advanced level of technology, use of DEs has been increasing rapidly over the last decade. Unlike placement of SEs, which simply requires craniotomy, DE placement generally requires stereotactic techniques such as frame-based stereotactic or robotic arm-based methods. However, such methods are not always available at every epilepsy center. We therefore invented guide pipes for accurate DE placement. With this guide pipe and neuronavigation-based (NB) DE placement system, we are able to place DEs accurately. However, the disadvantages of our original procedure were a relatively large skin incision and the difficulty in anchoring DEs. The purpose of this technical note is to introduce a method to perform NB DE placement with a smaller skin incision and simple anchoring procedure. As we could make the skin incision smaller and achieved easier anchoring of DEs using a titanium plate, we hope this procedure will help facilities to perform DE placement with neuronavigation systems.